Analysis of the Path of Protecting Enterprise Data Rights and Interests in China - Liu, Ruwei (Transactions on Social Science, Education and Humanities Research, 2023)
In the era of big data, data has gradually become the most important production factor and resource for enterprises, and disputes caused by enterprise data have also emerged endlessly. The existing framework for protecting enterprise data rights and interests in China has many shortcomings in theory and practice, which cannot properly solve problems and is not conducive to the development of the digital economy. Therefore, it is urgent to establish a protection method for enterprise data rights and interests. Due to the unique nature of enterprise data and its complex relationship with personal data, the protection of enterprise data rights cannot be generalized. According to the main forms of enterprise data disputes and the current situation of the main sources of enterprise data in China, it is appropriate to design corresponding rights from the perspectives of “enterprise-enterprise” and “enterprise-individual” to protect the rights and interests of enterprise data. Based on the establishment of restrictive property rights for enterprise data, when adjusting the rights and attributes of personal data, we aim to construct a path for protecting the rights and interests of Chinese enterprise data and promote the prosperity and development of the market economy and digital economy.